Thoughts of the hungarian settlement development in perspective of the smallest - Tóth , Tamás; Oláh , Izabella (Studia Mundi – Economica, 2019)
After reviewing the basics related to national settlement development, we present this topic from the perspective of the smallest settlements. During the examination of the small, tiny and pigmy settlements of Hungary, many results have been revealed in the last decades. These researches highlighted the characteristics of the settlements and tried to explore their main problems. We would like to contribute to these studies by discussing the opportunities for launching the Hungarian Village Program and by pointing out that there is still a lot of work to do in this areas. Numerous programs similar to Village Programs will be needed in order to solve existing and ongoing problems of these settlements.